{5,5′-Bis(diethylamino)-2,2′-[(2,2-dimethylpropane-1,3-diyl)bis(nitrilomethanylylidene)]diphenolato}dioxidomolybdenum(VI) - Kargar, Hadi (International Union of Crystallography, 2011)
In the title compound, [Mo(C(27)H(38)N(4)O(2))O(2)], the Mo(VI) atom is coordinated by two oxide O atoms and by two O and two N atoms of the tetradentate Schiff base ligand in a distorted octahedral geometry. The Mo—N bond trans to a terminal oxide group is significantly longer than the other Mo—N bond, which is attributed to the strong trans effect of the oxide O atom. The dihedral angle formed between the substituted benzene rings is 71.79 (14)°. One of the ethyl groups is disordered over two sets of sites, with a refined site-occupancy ratio of 0.588 (18):0.412 (18).